RELIABILITY OPTIMIZATION DESIGN ON SHEARER’S RANGING ARM GEAR TRANSMISSION SYSTEM - LI FengJiang; ZHANG Jie; LIAO YingHua; LI QingChen (Jixie qiangdu)
In the process of design shearer ’s ranging arm gear transmission system,by using the method of reliability design theory,derived gear strength and stress assumed to obey normal distribution when tooth surface contact fatigue strength and tooth root bending fatigue strength were taken as constraint conditions,and the volume of gear system as objective function,then genetic algorithm optimization toolbox of MATLAB was used to solve the optimization mathematic model. The results show that this method of optimization can improve gear transmission’s reliability,the volume and weight of gear transmission system are reduced too,which is beneficial to achieving products lightweight and reduceing production cost.